A Number of Cases in Iran Presenting with Coinheritance of Hemoglobin-H Disease and Beta-Thalassemia Minor. (2nd September 2016) - Zarei, Tahereh; Dehbozorgian, Javad; Imanifard, Jaber; Setoodegan, Fatemehsadat; Karimi, Mehran
Abstract: Thalassemias are a group of inherited hematological disorders caused by defects in the synthesis of one or more of the hemoglobin (Hb) chains. The β- and α-thalassemias are widespread throughout the Mediterranean region, the Middle East, and Southeast Asia including Iran. In this study, we report five patients known to carry a coinheritance of Hb H (β4) disease and β-thalassemia (β-thal) minor. There is a high prevalence of consanguineous marriages in our population and the high rate of thalassemia determinants can cause coinheritance of α- and β-thal. Therefore, it is of special interest to report coinheritance of Hb H disease and β-thal minor which could lead to misdiagnosis.